2009
DOI: 10.1007/s10600-010-9499-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxic activity of α-santonin amino-derivatives

Abstract: Previously unknown amino-derivatives of the natural sesquiterpene lactone α-santonin were synthesized. The activity of the products against several human tumor-cell lines was studied.Natural sesquiterpene lactones exhibit various types of biological activity including antitumor activity [1]. A study of structure-activity relationships has found that high cytotoxicity correlates with the presence of an exocyclic double bond in the lactone ring [2]. Furthermore, the presence of an activated double bond allows mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…272 7a-Hydroxyfrullanolide 293 has been biotransformed by several fungi with the aim of preparing metabolites with antibacterial activity. 273 The synthesis and cytotoxic activity of a-santonin amino-derivatives have been described, 274 whilst the epoxidation of ludartin and tourneforin has been studied. 275 A total synthesis of racemic axamide-1 and axisonitrile-1 has been reported.…”
Section: Elemanementioning
confidence: 99%
“…272 7a-Hydroxyfrullanolide 293 has been biotransformed by several fungi with the aim of preparing metabolites with antibacterial activity. 273 The synthesis and cytotoxic activity of a-santonin amino-derivatives have been described, 274 whilst the epoxidation of ludartin and tourneforin has been studied. 275 A total synthesis of racemic axamide-1 and axisonitrile-1 has been reported.…”
Section: Elemanementioning
confidence: 99%
“…Previously unknown amine derivatives (16-17) of α-santonin (1) were synthesized and studied for their activity against tumor human cell lines [19].…”
Section: Eurasianmentioning
confidence: 99%
“…[24] conducted the reactions of artemisinin (18) with ethanolamine. Authors isolated and identified corresponding lactam (19) from the reaction mixture. Reaction of artemisinin (18) with ethylene diamine led to a dimer (20).…”
Section: Artemisinin Isolating Technology and Ways To Obtain Its Deri...mentioning
confidence: 99%
“…To address this shortcoming, amines have been added to the α-methylene-γ-lactone substructure as an efficient way to enhance the water solubility of the parent molecules and to retain their biological activity. Amino-adducts have been prepared from the sesquiterpene lactones, alantolactone, 3 costunolide, 4 parthenolide ( 1 ), 57 α-santonin, 8 helenalin, 9 and ambrosin (Figure 1). 10 A key amino-adduct of parthenolide (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To address this shortcoming, amines have been added to the α-methylene-γ-lactone substructure as an efficient way to enhance the water solubility of the parent molecules and to retain their biological activity. Amino-adducts have been prepared from the sesquiterpene lactones, alantolactone, costunolide, parthenolide ( 1 ), α-santonin, helenalin, and ambrosin (Figure ) . A key amino-adduct of parthenolide (i.e., DMAPT or LC-1) has advanced into clinical studies in humans despite a long-standing bias in medicinal chemistry against using molecules with a potential covalent mechanism of action in clinical trials .…”
Section: Introductionmentioning
confidence: 99%